A study of waterproofing material on toilet / bathroom area / Abdul Razak Mahal - Mahal, Abdul Razak (Faculty of Architecture , Planning and Surveying, 2005)
The use of waterproofing in construction industry was established in October 1837 by Mr. Claridge in investigation of the possibilities of water proof material for construction use. Then, further investigation was done repeatedly to find the best techniques and materials for the use of waterproofing materials in construction industry. It is has been used some year 1845 and by the year 1860, it had become one of the most indispensable technique in the construction industry. The materials and technologies of water proofing has developed vastly into world usage in new and existing buildings both internally and externally.Generally, waterproofing is a technique with the ability to resist the penetration of water into the building or any part of building elements.This characteristic is important to avoid any dampness to the building interiors which is one of the most causes of building defect. It is often rated first among the most causes of construction complaints,continually creating unnecessary problems. No single building component producing such enormous problems has so little standardization on which to base improvements. The construction industry has yet to adopt the principle that the entire exterior facade must be treated as single cohesive unit elements in which all individual components are transitioned into one another in completely waterproof detailing. Different types of waterproofing materials are useful for different types of buildings, the usage, the weather type, etc. The installation process must catch up with technology advances in materials and systems.These manufactured products do not produce leakage; it is rather the improper detailing or lack thereof in integrating products into a structure that causes the problem. Waterproofing manufacturers must also become more responsive in providing information on the correct details for transitions and termination methods used to incorporate their materials into composite building elements.